Social-ecological performance of collaborative wildlife governance : the case of Swedish moose management - Dressel, Sabrina (2020)
Natural resources such as wildlife are part of social-ecological systems, which are characterized by inherent complexity, uncertainty, and changes. Therefore, collaborative, decentralized, and adaptive approaches tend to be preferred in environmental governance. Despite extensive research efforts, central questions about ‘what works where, and why’ remain. My thesis helps bridge this knowledge gap with insights from Swedish moose (Alces alces) management. In 2012, Sweden implemented a multi-level collaborative governance regime to manage moose in accordance with the ecosystem approach. This involved establishing Moose Management Areas (MMA), which are led by Moose Management Groups (MMG) consisting of landowner and hunter representatives. The aim of my thesis was to analyse the effects of context and institutional design on the social-ecological performance of the moose management system. I based my analyses on surveys, interviews, and workshops with actors on different governance levels, which I combined with information from management plans and ecological monitoring. My results revealed spatial and functional misfits created by the design and implementation of the system. In northern Sweden, large MMAs were created to match seasonal moose migration. This creates challenges for collaboration because large areas require more time investment from MMGs and processes that enable the integration of many stakeholders. Functional misfits occur in southern Sweden, where land use is more diverse and several other ungulate species co-exist with moose; both of these factors adversely affected moose quota fulfilment. Adaptations are needed to overcome these misfits. I found that linking and bridging social capital between governance levels were significant determinants of actors’ perceived adaptive capacity. On the local level, perceptions of fairness also contributed, while sufficient resources and knowledge were important for MMGs. ‘Good examples’ (i.e. MMAs that achieved good social and ecological outcomes) were ...